Indigenous rights-based approaches to decolonising research methodologies in settler colonial contexts - Peter Anderson; Zane M. Diamond; Thu Pham; Angela Baeza Peña; Carla Tapia; Levon Blue; Melanie Saward; Angelina Hurley; Kate Pecar; Amanda Kelly; Owen Forbes; Veronica Goerke; et al. (Frontiers in Research Metrics and Analytics)
IntroductionIndigenous knowledge and perspectives continue to be misrepresented and misunderstood in settler colonial states, including within academic circles. This is particularly the case in the field of research, where non-Indigenous researchers continue to design and conduct research in their field of expertise without appropriate collaboration and guidance from Indigenous experts.MethodWe explore the Indigenous rights-based approach (IRBA) as a means of decolonising research methodologies, focussing on the Australian context as a case study, where an Aboriginal Australian higher education expert has worked in a dyadic relationship with one Aboriginal and 16 non-Aboriginal subject experts to develop their knowledge, skills, and understanding of how to employ IBRA in their research. After working collaboratively, it became possible to analyse the similarities and differences in the use of IBRA across various fields of study.ResultsOur analysis reveals five key aspects that were revealed during the implementation of the Indigenous rights-based approach: (1) Indigenous People as Data, (2) Protocols of engagement, (3) Privileging Indigenous Knowledge Systems, (4) Community Benefit, and (5) Tackling Doctoral Research Training.DiscussionWe found that an Indigenous rights-based approach is crucial for decolonising research in settler colonial states such as Australia. Working in a dyadic partnership between an Indigenous higher education expert and academic researchers across several disciplines, we have seen an emergent approach to researching with Indigenous Peoples that allows non-Aboriginal researchers to work with Indigenous people in a manner that is ethical, relevant, and significant for Indigenous communities, contributing to place-based reconciliation and Indigenous community empowerment.ConclusionWe recommend how non-Indigenous researchers can collaborate with their universities to successfully implement an IRBA. Critically, this will require each university to employ Indigenous higher education experts who will lead and support professional development in research with non-Aboriginal people and communities. This will require a fundamental shift in how research is conceptualised, conducted, and disseminated.